2011
DOI: 10.5704/moj.1111.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Late Collapse of Distal Radius Fractures Factors Predicting Late Collapse of Distal Radius Fractures

Abstract: Background: Although fractures of the distal radius are a common clinical presentation, many factors affect instability of these injuries. The aim of this study was to assess the influence of age, sex, distal radial ulnar joint injury (DRUJ), ulnar styloid fracture, and dorsal displacement in late collapse of distal radius fractures. Methods: Three hundred twenty-nine patient fractures were measured for dorsal tilt, radial inclination and ulnar variance after reduction and 2 months later. Reduction loss was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Additionally, the definition of an acceptable ulnar variance provided a wide variety in answers. Although in literature ulnar variance is widely used to predict instability [12, 31] and radiographic alignment following operative or non-operative treatment of distal radius fractures [22, 3234], our results question whether ulnar variance is as well-known as we think it is and how it is best used in distal radius fracture management. Moreover, there was consensus among both surgeons and residents on an intra-articular step-off and gap of less than 2 mm, indicating an acceptable reduction.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, the definition of an acceptable ulnar variance provided a wide variety in answers. Although in literature ulnar variance is widely used to predict instability [12, 31] and radiographic alignment following operative or non-operative treatment of distal radius fractures [22, 3234], our results question whether ulnar variance is as well-known as we think it is and how it is best used in distal radius fracture management. Moreover, there was consensus among both surgeons and residents on an intra-articular step-off and gap of less than 2 mm, indicating an acceptable reduction.…”
Section: Discussionmentioning
confidence: 81%
“…Several factors have already been reported to predict the outcome of the volar plating system for the DRF. Age, AO classification, distal radial ulnar joint injury, ulnar styloid fracture and initial displacement are predictive of reduction loss and knowing that these factors are predictive can aid in early decision-making as to the method of treatment [10, 11]. Age, sex and size of dorsal cortex comminution can be used to predict the late dorsal tilt angulation of distal articular surface of radius at the end of the immobilization [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are already some factors reported to predict the functional outcomes following DRF. Myderrizi N [10] found that factors such as age, AO classification, distal radial ulnar joint injury, ulnar styloid fracture and initial displacement are predictive of reduction loss. Belloti JC et al [11] also found that ulnar styloid fracture may be a predictive factor of worse functional outcome for DRF.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that worse AO fracture types (Group C fractures) may lead to an increased risk of loss of reduction in closed management [17]. However, in operative treatment, its impact on restoration of normal radiographic parameters and early loss of reduction has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%